Teddy Bear Tales - Teddy Bear Tales (Bookmark Limited, 1999)
This delightful little collection contains a feast of teddy bear tales old and new. and every page is colorfully illustrated by leading children's artists, accompanied by a read along audio tape
Keywords: Children Fiction Book